Proposta de um cicloconversor híbrido de entrada trifásica e saída monofásica com baixo índice de distorções harmônicas da tensão de saída - Guimarães, Érico Chagas (2016)
This work consists of a power electronics project that aims to implement a hybrid six pulses Cycloconverter with three phase input and single-phase output. The proposed methodology is based on the series association of Cycloconverter with a DC-DC high dynamics converter. This DC-DC converter is designed to process the minimum amount of energy possible, aiming to mitigate harmonic distortion of the output voltage. To illustrate the developed technique, the simulations will be presented. They confirmed the application's functionality and show the power stage of the two converters as well as digital and analog control techniques used for the correct operation of the Cycloconverter and compensator converter, respectively. This work also presents details of the prototype built in the laboratory aiming confirm the operation of the idealized circuit. Finally, experimental results in different operation modes are present.